PENGARUH KESIAPAN BELAJAR DAN KEMAMPUAN BERTANYA TERHADAP HASIL BELAJAR STATISTIK MAHASISWA STKIP KUMALA LAMPUNG METRO - Noviansyah, Wahyu (Universitas Dr. Soetomo, 2019)
This research is aimed to identify the influence of learning preparation and questioning skill toward statistics learning result of STKIP Kumala Lampung Metro Students. The population in this research is all students of Economy education study program who have passed statistics lecture, and the sample is 28 students which are chosen by purposive random sampling technique. The data collecting techniques are done by a questionnaire to knowing the students’ learning readiness and ability to ask quation and documentation method to knowing statistics lecture result. The multiple linear regression is used as data analysis in this research.The research result showed; firstly, there is positive and significant influence of learning readiness toward statistics learning result with 0,376 for the correlation coefficient, 0,142 for the determinant coefficient and = 2,104 + 0,068X1 as the regression equation. Secondly, there is also positive and significant influence of ability to ask toward statistics learning result with 0,387 as the coefficient correlation, 0,149 as determinant coefficient, and = 1,431 + 0,085X2 as the regression equation. Thirdly, in this research also, there is positive and significant influence of learning readiness and ability to ask toward statistics learning result with 0,476 as the correlation coefficient, and 0,227 as determinant coefficient and = -0,936 + 0,052X1 +0,067X2 for the regression equation.